21st Century International Higher Education Hotspots: International Student Mobility Growth in Non-Traditional Destination Countries - Johnson , Karin (Journal of International Students, 2020)
The Institute of International Education (IIE) 2018 Open Doors report highlighted that the United States is the leading international education destination, having hosted about 1.1 million international students in 2017 (IIE, 2018a). Despite year over year increases, U.S. Department of State (USDOS, 2018) data show that for a third year in a row, international student visa issuance is down. This is not the first decline. Student visa issuance for long-term academic students on F visas also significantly dropped following the 9/11 attacks (Johnson, 2018). The fall in issuances recovered within 5 years of 2001 and continued to steadily increase until the drop in 2016. Taken together, the drops in international student numbers indicate a softening of the U.S. international education market. In 2001, the United States hosted one out of every three globally mobile students, but by 2018 it hosted just one of five (IIE, 2018b). This suggests that over the past 20 years, the United States has lost a share of mobile students in the international education market because they’re enrolled elsewhere. The Rise of Nontraditional Education Destination Countries Unlike the United States, the percentage of inbound students to other traditional destinations such as Canada, the United Kingdom, France, and Germany, has remained stable since the turn of the 21st century. Meanwhile, nontraditional countries like the United Arab Emirates (UAE) and Russia are garnering more students and rising as educational hotspots (Knight, 2013). The UAE and Russia annually welcome thousands of foreign students, respectively hosting over 53,000 and 194,000 inbound international university students in 2017 (UNESCO Institute for Statistics, 2019). This is not happenstance. In the past 5 years, these two countries, among others, have adopted higher education internationalization policies, immigration reforms, and academic excellence initiatives to attract foreign students from around the world. The UAE is one of six self-identified international education hubs in the world (Knight, 2013) and with 42 international universities located across the emirates, it has the most international branch campuses (IBCs) worldwide (Cross-Border Education Research Team, 2017). Being a country composed of nearly 90% immigrants, IBCs allow the UAE to offer quality higher education to its non-Emirati population and to attract students from across the Arab region and broader Muslim world. National policy and open regulations not only encourage foreign universities to establish IBCs, they alsoattract international student mobility (Ilieva, 2017). For example, on November 24, 2018, the national government updated immigration policy to allow foreign students to apply for 5-year visas (Government.ae, 2018). The Centennial 2071 strategic development plan aims for the UAE to become a regional and world leader in innovation, research, and education (Government.ae, 2019), with the long-term goal of creating the conditions necessary to attract foreign talent. Russia’s strategic agenda also intends to gain a greater competitive advantage in the world economy by improving its higher education and research capacity. Russia currently has two higher education internationalization policies: “5-100-2020” and “Export Education.” The academic excellence project, known as “5-100-2020,” funds leading institutions with the goal to advance five Russian universities into the top 100 globally by 2020 (Ministry of Science and Higher Education of the Russian Federation, 2018). The “Export Education” initiative mandates that all universities double or triple the number of enrolled foreign students to over half a million by 2025 (Government.ru, 2017). These policies are explicitly motivated by boosting the Russian higher education system and making it more open to foreigners. Another growing area is international cooperation. Unlike the UAE, Russia has few IBCs, but at present, Russian universities partner with European and Asian administrators and government delegates to create dual degree and short-term programs. Historically, Russia has been a leading destination for work and education migrants from soviet republics in the region, but new internationalization policies are meant to propel the country into the international education market and to attract international students beyond Asia and Europe. Future Trends in 21st Century International Education Emerging destination hotspots like the UAE and Russia are vying to become more competitive in the global international higher education market by offering quality education at lower tuition rates in safe, welcoming locations closer to home. As suggested by the softening of the U.S. higher education market, international students may find these points attractive when considering where to study. Sociopolitical shifts that result from events such as 9/11 or the election of Donald Trump in combination with student mobility recruitment initiatives in emerging destinations may disrupt the status quo for traditional countries by rerouting international student enrollment to burgeoning educational hotspots over the coming decades.